2010
DOI: 10.1111/j.1439-0442.1977.tb01582.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Increasing Amounts of NH4CI in the Diet on Ammonia Detoxication in Rats

Abstract: Summary The ability of rats to adapt to better detoxication of ammonia when food with ammonium chloride added was continuously available, was examined. The rats were divided into 5 feeding groups. Group I (control group) was given low‐protein food (5 per cent of casein); Groups II to V were given the same food with the addition of 1, 2, 4 and 8 per cent of ammonium chloride, respectively. The period of feeding with respective foods was 7 days. The amount of ammonium chloride in the food was in inverse proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…Our experiment demonstrated that rats fed a diet containing ammonium acetate (about 20 O / o of total nitrogen) have a lower plasma IRI level than animals fed the natural diet (11). This effect was similar to the one observed in rats (15) and sheep ( 2 ) during intravenous infusion of ammonium chloride.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our experiment demonstrated that rats fed a diet containing ammonium acetate (about 20 O / o of total nitrogen) have a lower plasma IRI level than animals fed the natural diet (11). This effect was similar to the one observed in rats (15) and sheep ( 2 ) during intravenous infusion of ammonium chloride.…”
Section: Discussionsupporting
confidence: 85%
“…Studies were conducted on 120 Wistar rats divided into two groups, one given a diet containing 15 O/o casein and 3 O/o ammonium acetate (I) and the other a similar diet without ammonium acetate (11). The animals were fed these diets ad libitum for seven days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This thesis has been confirmed by KULASEK (21) who observed the accelerated elimination of ammonia from the blood, after the intravenous injection of ATP to rabbits. The author's investigations upon the adaptation of rats to ammonium ion loading have shown that the greatest activity of ornithine transcarbamylase and arginase in the liver, as well as the highest level of 'ATP in the blood, muscles and liver appeared in animals with the greatest toleration to this ion (23). In view of these investigation it is interesting to determine whether an increase of ATP level in the organism can change the toleraticn of rats to the ammonium ion.…”
Section: Introductionmentioning
confidence: 99%